Development and validation of a multiplex PCR assay with melt curve analysis for detecting simian Plasmodium in wild Macaca fascicularis - Thitiluck Swangsri; Rucksak Rucksaken; Wanat Sricharern; Wang Nguitragool; Naowarat Saralamba (Scientific Reports)
Abstract Accurate and sensitive detection of simian malaria parasites is essential for surveillance and risk assessment of zoonotic malaria. We developed and validated a SYBR Green-based real-time PCR assay targeting the msp1 gene to detect and differentiate P. knowlesi, P. cynomolgi, and P. inui. Species-specific amplification was confirmed through distinct melting temperature (Tm) profiles. The assay demonstrated high analytical sensitivity, with a limit of detection of 10 copies/µL, excellent specificity with no cross-reactivity, and strong reproducibility, with low coefficients of variation for both cycle threshold (Ct) and Tm values. Amplification efficiency was within acceptable ranges, with R2 > 0.90 across standard curves. The assay was evaluated using 191 archived blood samples from wild M. fascicularis collected across three provinces in Thailand, with P. knowlesi detected in two samples. Both positive detections were confirmed by nested PCR and sequencing. This assay offers a rapid, cost-effective, and reliable tool for detecting simian malaria parasites in laboratory analyses and has potential for further application in field surveillance.